Pengaruh Influencer Endorsement dan Brand Image terhadap Minat Beli Produk Xl Prabayar di Kota Surabaya dengan Brand Trust sebagai Variabel Mediasi - Garut, Albertyano Gilang; Olanda, Aditiya (Universitas Batanghari Jambi, 2025)
The aim of this research is to determine influencer endorsement and brand image on consumer buying interest in prepaid XL products in the city of Surabaya with brand trust as a mediating variable. This research method is a quantitative approach with a survey research type and the sampling technique is probability sampling. The population in this study were paid SIM-Card consumers in the city of Surabaya, so the selected sample was 85 consumers calculated from the Slovin formula. The analysis was carried out by distributing questionnaires, then the analytical tool used in this research was component-based Structural Equation Modeling (SEM) with the Partial Least Square (PLS) analysis tool. The results of this research conclude that the influencer endorsement and brand image variables have a positive and significant effect on the brand trust variable for XL prepaid products. The brand trust variable influences the interest variable in purchasing prepaid XL products. Thus, the brand trust variable can mediate the relationship between the influencer endorsement and brand image variables on the interest variable in purchasing prepaid XL products in the city of Surabaya.